The effect of using different rinsing angles on the micro-tensile bond strength of the sealant to the etched enamel - Hossein Afshar; Yahya Baradaran Nakhjavani; Rahil Ahmadi (Wolters Kluwer Medknow Publications, 2014)
Background: Attempts to enhance bond strength of the sealant have been among the most important sides of dental research. Aim: The purpose of the present study was to evaluate the effect of using different rinsing angles on the micro-tensile bond strength of the sealant to the etched enamel. Settings and Design: Experimental study. Materials and Methods: Sixty first-premolars were randomly assigned to six groups based on the rinsing angle applied (15°, 30°, 45°, 60°, 75°, and 90°). Following etching and rinsing, a 4-mm height build up of sealant material was created. Bonded specimens were sectioned into sticks (1 Χ 1 mm), which were subjected to micro-tensile bond strength, testing at a cross-head speed of 0.5 mm/min. Statistical Analysis Used: The data were analyzed by Kolmogorov-Smirnov and post-hoc Tukey test. Results: The tensile bond strength in specimens rinsed at 90° were statistically higher compared to those rinsed at 15° and 30° (P < 0.05), and increasing the angle from 15° to 90° was correlated with a reduction in the number of specimens with adhesive failures. Conclusions: Rinsing the conditioned enamel surface at 90° may improve the bond strength and retention of the sealant.